Yokan
By integrating anionically modified cellulose nanofibers into the yokan recipe, the issue of red bean paste settling in yokan is resolved, resulting in a more visually appealing and flavorful dessert.
Patent Information
- Application Number
- JP2021045619
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-19
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-03-19
AI Technical Summary
Yokan made from red bean paste, such as azuki beans, can suffer from the red beans settling at the bottom when cooled and hardened, leading to a poor appearance and flavor.
Incorporating cellulose nanofibers, specifically anionically modified cellulose nanofibers with a carboxyl group or carboxyalkyl group, into the yokan recipe to prevent the bean paste from settling.
The use of cellulose nanofibers ensures that the adzuki beans and other components remain evenly distributed within the yokan, enhancing both its appearance and flavor.
Abstract
Description
[Technical field]
[0001] The present invention relates to a yokan containing cellulose nanofibers. [Background technology]
[0002] Yokan is made by adding agar, sugar, and water to bean paste made from red beans and other beans, heating it to dissolve the agar and sugar, kneading it, and then cooling it to harden it.
[0003] As a method for improving the texture of yokan, a mizu yokan-style filling containing thickening polysaccharides such as xanthan gum or tamarind gum has been proposed (Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2007-202520 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0005] However, when yokan made from tsubu-an (bean paste) such as azuki beans, especially mizu-yokan, is cooled and solidified, the azuki beans tend to settle to the bottom, which can deteriorate the appearance and flavor.
[0006] Therefore, an object of the present invention is to provide a yokan (jelly bean paste) which has a good appearance and an excellent texture, since the bean paste, especially the tsubu-an paste, does not settle to the bottom. [Means for solving the problem]
[0007] As a result of extensive research into achieving this object, the inventors discovered that incorporating cellulose nanofibers (CNF) is effective, and thus completed the present invention.
[0008] The present invention provides the following: (1) Yokan containing cellulose nanofibers. (2) The yokan according to (1), wherein the cellulose nanofiber is anionically modified cellulose nanofiber. (3) The yokan according to (1) or (2), wherein the anion-modified cellulose nanofiber is a cellulose nanofiber having a carboxyl group or a cellulose nanofiber having a carboxyalkyl group. (4) The yokan according to (3), wherein the anion-modified cellulose nanofiber is a carboxymethylated cellulose nanofiber having a degree of carboxymethyl substitution in the range of 0.01 to 0.50. (5) The yokan according to any one of (1) to (4), further comprising carboxymethyl cellulose. Effect of the Invention
[0009] According to the present invention, it is possible to provide a yokan (jelly jelly), particularly a mizu yokan (water yokan), made from tsubu-an (bean paste) of red beans or the like, in which the red beans, their seed coats or fruits do not settle to the bottom and which has excellent appearance and flavor. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention will be described in detail below. In the present invention, "to" includes the end values. That is, "X to Y" includes the values X and Y at both ends.
[0011] The yokan of the present invention is a paste yokan or a mizu yokan containing bean paste, agar, and a sweetener, and is produced by heating to a temperature at which the agar dissolves, pouring the liquid raw material into a mold, and cooling it to solidify. As the paste, bean paste made from beans such as red beans, soybeans, and white kidney beans, potatoes such as sweet potatoes, chestnuts, etc., which are usually used as raw materials for bean paste, can be used. As the paste, various forms such as koshi-an, tsubu-an, sanashi-an, and kneaded bean paste can be used. As the sweetener, sugars, honey, stevioside, revautioside, and other commonly used sweeteners can be used. More specifically, as the sugar, monosaccharides such as glucose and fructose, disaccharides such as maltose, sucrose, and lactose, as well as various sugars in powder or liquid such as isomerized sugar, starch syrup, reduced starch syrup, and sugar alcohols can be used. These sugars may be used alone or in combination of two or more.
[0012] Also, various fruits, dried fruits such as raisins and dried cherries, and nuts such as almonds, peanuts, chestnuts and walnuts may be added.
[0013] (Cellulose nanofiber) In the present invention, the amount of cellulose nanofibers is preferably 0.01 to 5 mass% of the yokan (including water) calculated as solid content, more preferably 0.05 to 3 mass%, and even more preferably 0.1 to 2 mass%. If the amount of cellulose nanofibers is less than 0.01 mass%, the effect of preventing grains such as red beans from settling at the bottom of the yokan is insufficient, and even if it is added in excess of 5 mass%, the effect of preventing settling hits a plateau.
[0014] In the present invention, cellulose nanofibers (hereinafter sometimes referred to as CNF) are fine fibers with a fiber width of about 1 to 500 nm, which are made by pulp, a cellulose-based raw material, being refined to the nanometer level. The average fiber diameter and average fiber length of cellulose nanofibers can be obtained by averaging the fiber diameters and fiber lengths obtained from the observation of each fiber using an atomic force microscope (AFM) or a transmission electron microscope (TEM). The average aspect ratio of cellulose nanofibers is usually 50 or more. There is no particular upper limit, but it is usually 1000 or less. The average aspect ratio can be calculated by the following formula: Aspect ratio = average fiber length / average fiber diameter Cellulose nanofibers are obtained by applying mechanical force to pulp to make it finer, and can be obtained by defibrating unmodified cellulose or modified cellulose such as carboxylated cellulose (also called oxidized cellulose), carboxymethylated cellulose, anionically modified cellulose such as cellulose with a phosphate ester group introduced therein, or cationized cellulose. The average fiber length and average fiber diameter of the fine fibers can be adjusted by oxidation treatment and defibration treatment. In the present invention, it is preferable to use carboxymethylated (CM) cellulose nanofibers obtained by defibrating carboxymethylated cellulose obtained by carboxymethylation treatment.
[0015] (Cellulose raw material) Examples of cellulose raw materials for producing cellulose nanofibers used in the present invention include those originating from plant materials (e.g., wood, bamboo, hemp, jute, kenaf, agricultural waste, cloth, pulp), animal materials (e.g., sea squirts), algae, and microorganisms (e.g., acetic acid bacteria (Acetobacter)). Pulps include softwood unbleached kraft pulp (NUKP), softwood bleached kraft pulp (NBKP), hardwood unbleached kraft pulp (LUKP), hardwood bleached kraft pulp (LBKP), softwood unbleached sulfite pulp (NUSP), softwood bleached sulfite pulp (NBSP), thermomechanical pulp (TMP), recycled pulp, waste paper, and the like. All of these can be used, but cellulose fibers derived from plants or microorganisms are preferred, and cellulose fibers derived from plants are more preferred.
[0016] (Carboxymethylation) In the present invention, when carboxymethylated cellulose nanofibers are used, the carboxymethylated cellulose may be obtained by carboxymethylating the above-mentioned cellulose raw material by a known method, or a commercially available product may be used. In either case, the degree of carboxymethyl substitution per anhydrous glucose unit of cellulose is preferably 0.01 to 0.50. An example of a method for producing such carboxymethylated cellulose can be mentioned as follows. Cellulose is used as a starting material, and 3 to 20 times by mass of water or a lower alcohol is used as a solvent. Specifically, water, methanol, ethanol, N-propyl alcohol, isopropyl alcohol, N-butanol, isobutanol, tertiary butanol, etc. can be used alone or in combination of two or more kinds. When a mixed solvent of water and a lower alcohol is used, the mixing ratio of the lower alcohol is 60 to 95% by mass. As a mercerizing agent, 0.5 to 20 times by mole of an alkali metal hydroxide per anhydrous glucose residue of the starting material, specifically sodium hydroxide or potassium hydroxide, is used. The starting material, solvent, and mercerizing agent are mixed, and a mercerization treatment is carried out at a reaction temperature of 0 to 70° C., preferably 10 to 60° C., for a reaction time of 15 minutes to 8 hours, preferably 30 minutes to 7 hours. Then, a carboxymethylating agent is added at 0.05 to 10.0 times the moles per glucose residue, and an etherification reaction is carried out at a reaction temperature of 30 to 90° C., preferably 40 to 80° C., for a reaction time of 30 minutes to 10 hours, preferably 1 hour to 4 hours.
[0017] <Carboxymethylated cellulose nanofiber> The carboxymethylated cellulose nanofibers of the present invention maintain at least a part of their fibrous shape even when dispersed in water. That is, when an aqueous dispersion of the carboxymethylated cellulose nanofibers is observed under an electron microscope, a fibrous substance can be observed. Furthermore, when the carboxymethylated cellulose nanofibers are measured by X-ray diffraction, a peak of cellulose type I crystals can be observed.
[0018] <Crystallization degree of cellulose type I> The crystallinity of cellulose in the carboxymethylated cellulose nanofiber used in the present invention is 40% or more, preferably 50% or more, for crystalline type I. When the crystallinity of cellulose type I is as high as 40% or more, the proportion of cellulose that does not dissolve in a solvent such as water and maintains its crystalline structure is high, so that the thixotropy is high and it becomes suitable for viscosity adjustment applications such as thickeners. In addition, for example, but not limited to, when added to a gel-like substance (e.g., food, cosmetics, etc.), it has the advantage of being able to impart excellent shape retention. The crystallinity of cellulose can be controlled by the concentration of the mercerizing agent, the temperature during treatment, and the degree of carboxymethylation. Since a high concentration of alkali is used in mercerization and carboxymethylation, cellulose type I crystals are easily converted to type II, but the desired crystallinity can be maintained by adjusting the degree of denaturation by adjusting the amount of alkali (mercerizing agent) used. There is no particular upper limit to the crystallinity of cellulose type I. In reality, it is thought that the upper limit is about 90%.
[0019] The method for measuring the crystallinity of cellulose type I of carboxymethylated cellulose nanofiber is as follows: The sample is placed in a glass cell and measured using an X-ray diffraction measuring device (LabX XRD-6000, manufactured by Shimadzu Corporation). The degree of crystallinity is calculated using the method of Segal et al., and is calculated from the diffraction intensity of the 002 plane at 2θ = 22.6° and the diffraction intensity of the amorphous part at 2θ = 18.5° using the diffraction intensity of the X-ray diffraction pattern at 2θ = 10° to 30° as the baseline, according to the following formula. Xc = (I002c - Ia) / I002c x 100 Xc = Crystallinity of cellulose type I (%) I002c: 2θ=22.6°, diffraction intensity of 002 plane Ia: 2θ=18.5°, diffraction intensity of the amorphous part.
[0020] The proportion of type I crystals in carboxymethylated cellulose nanofibers is usually the same as that in the carboxymethylated cellulose before it is made into nanofibers.
[0021] <Degree of carboxymethyl substitution> The carboxymethylated cellulose nanofibers used in the present invention have a carboxymethyl substitution degree per anhydrous glucose unit of cellulose of 0.50 or less. If the carboxymethyl substitution degree exceeds 0.50, it is considered that the cellulose dissolves in water and cannot maintain the fiber shape. In consideration of the operability, the substitution degree is preferably 0.01 to 0.50, more preferably 0.02 to 0.50, even more preferably 0.05 to 0.40, and even more preferably 0.10 to 0.40. By introducing a carboxymethyl group into cellulose, the cellulose particles electrically repel each other, so that the cellulose can be defibrated into nanofibers. However, if the carboxymethyl substitution degree per anhydrous glucose unit is less than 0.01, the defibration becomes insufficient, and cellulose nanofibers with high transparency may not be obtained. In the conventional aqueous medium method, it was difficult to obtain carboxymethylated cellulose nanofibers having a crystallinity of cellulose I type of 60% or more when the degree of carboxymethyl substitution was in the range of 0.20 to 0.40, but the present inventors have found that it is possible to produce carboxymethylated cellulose nanofibers having a degree of carboxymethyl substitution in the range of 0.20 to 0.40 and a crystallinity of cellulose I type of 60% or more, for example, by the method described below. The degree of carboxymethyl substitution can be adjusted by controlling the amount of the carboxymethylating agent to be reacted, the amount of the mercerizing agent, the composition ratio of water to the organic solvent, etc.
[0022] In the present invention, the anhydroglucose unit means each anhydroglucose (glucose residue) constituting cellulose. The degree of carboxymethyl substitution (also called the degree of etherification) indicates the ratio of hydroxyl groups in the glucose residues constituting cellulose that are substituted with carboxymethyl ether groups (the number of carboxymethyl ether groups per glucose residue). The degree of carboxymethyl substitution may be abbreviated as DS.
[0023] The method for measuring the degree of carboxymethyl substitution is as follows: Weigh out approximately 2.0 g of the sample and place it in a 300 mL Erlenmeyer flask with a stopper. Add 100 mL of a solution of 1000 mL of nitric acid methanol and 100 mL of special-grade concentrated nitric acid, and shake for 3 hours to convert the salt of carboxymethylated cellulose nanofiber (CMC) to H-CMC (hydrogen-type carboxymethylated cellulose nanofiber). Weigh out 1.5 to 2.0 g of the bone-dry H-CMC and place it in a 300 mL Erlenmeyer flask with a stopper. Moisten the H-CMC with 15 mL of 80% methanol, add 100 mL of 0.1 N-NaOH, and shake at room temperature for 3 hours. Using phenolphthalein as an indicator, back-titrate the excess NaOH with 0.1 N-H2SO4, and calculate the degree of carboxymethyl substitution (DS value) using the following formula. A=[(100×F'-0.1N-H2SO4(mL)×F)×0.1] / (H-CMC (bone dry mass (g)) Degree of carboxymethyl substitution = 0.162 x A / (1-0.058 x A) F': Factor of 0.1N-H2SO4 F: Factor of 0.1N NaOH.
[0024] The degree of carboxymethyl substitution in the carboxymethyl cellulose nanofibers is usually the same as the degree of carboxymethyl substitution in the carboxymethyl cellulose before being made into nanofibers.
[0025] <Fiber diameter, aspect ratio> The carboxymethyl cellulose nanofibers used in the present invention have a nanoscale fiber diameter. The average fiber diameter is preferably 3 nm to 500 nm, more preferably 3 nm to 150 nm, more preferably 3 nm to 20 nm, more preferably 5 nm to 19 nm, and even more preferably 5 nm to 15 nm.
[0026] The aspect ratio of the carboxymethylated cellulose nanofiber is not particularly limited, but is preferably 350 or less, more preferably 300 or less, more preferably 200 or less, more preferably 120 or less, more preferably 100 or less, and even more preferably 80 or less. When the aspect ratio is 350 or less, the fibers are not excessively long, and the fibers are less entangled, which reduces the generation of lumps (lumps) of cellulose nanofibers, making it suitable for use as an additive. In addition, since the fluidity is high, it is easy to use even at high concentrations, and there is an advantage that it is easy to use in applications requiring a high solid content. The lower limit of the aspect ratio is not particularly limited, but is preferably 25 or more, more preferably 30 or more. When the aspect ratio is 25 or more, the fibrous shape has an effect of improving thixotropy. The aspect ratio of the carboxymethylated cellulose nanofiber can be controlled by the mixing ratio of the solvent and water during carboxymethylation, the amount of chemicals added, and the degree of carboxymethylation, and can be produced, for example, by the production method described below.
[0027] The average fiber diameter and average fiber length of carboxymethylated cellulose nanofibers can be measured by analyzing 200 randomly selected fibers using an atomic force microscope (AFM) if the diameter is 20 nm or less, or a field emission scanning electron microscope (FE-SEM) if the diameter is 20 nm or more, and calculating the average. The aspect ratio can be calculated using the following formula: Aspect ratio = average fiber length / average fiber diameter.
[0028] (Defibrilization) The defibration of the cellulose raw material may be carried out before or after the denaturation treatment of the cellulose raw material. Furthermore, the defibration may be carried out once or multiple times. If the defibration is carried out multiple times, each defibration may be carried out at any time.
[0029] The device used for defibration is not particularly limited, but examples include devices of high-speed rotation type, colloid mill type, high pressure type, roll mill type, ultrasonic type, etc., and a high-pressure or ultra-high pressure homogenizer is preferable, and a wet high-pressure or ultra-high pressure homogenizer is more preferable. The device is preferably capable of applying a strong shear force to the cellulose raw material or modified cellulose (usually a dispersion liquid). The pressure that the device can apply is preferably 50 MPa or more, more preferably 100 MPa or more, and even more preferably 140 MPa or more. The device is preferably a wet high-pressure or ultra-high pressure homogenizer that can apply the above pressure to the cellulose raw material or modified cellulose (usually a dispersion liquid) and can apply a strong shear force. This allows efficient defibration.
[0030] When defibrating a dispersion of cellulose raw material, the solid content concentration of the cellulose raw material in the dispersion is usually 0.1% by mass or more, preferably 0.2% by mass or more, and more preferably 0.3% by mass or more. This ensures that the amount of liquid relative to the amount of cellulose fiber raw material is appropriate and efficient. The upper limit is usually 10% by mass or less, and preferably 6% by mass or less. This allows fluidity to be maintained.
[0031] Prior to defibration (preferably with a high-pressure homogenizer) or, if necessary, prior to dispersion treatment, a pretreatment may be carried out as necessary. The pretreatment may be carried out using a mixing, stirring, emulsifying, or dispersing device such as a high-speed shear mixer.
[0032] (Dry) The cellulose nanofibers used in the present invention can be used in the state of the dispersion obtained after defibration, but can also be dried and redispersed in water as necessary. The drying method is not particularly limited, and known methods such as freeze drying, spray drying, tray drying, drum drying, belt drying, a method of thinly spreading on a glass plate or the like and drying, fluidized bed drying, microwave drying, and heated fan reduced pressure drying can be used. After drying, the cellulose nanofibers may be pulverized using a cutter mill, hammer mill, pin mill, jet mill, or the like as necessary. The method of redispersing in water is also not particularly limited, and known dispersion devices can be used.
[0033] The cellulose nanofibers used in the present invention may be in the form of a dispersion or powder, but from the viewpoint of excellent workability during the production of yokan, it is preferable to use the cellulose nanofibers in the form of a dispersion.
[0034] The cellulose nanofiber of the present invention may contain other components as necessary. For example, when producing a powder, it is preferable to add a water-soluble polymer to the cellulose nanofiber dispersion before drying, as this improves redispersibility.
[0035] <Water-soluble polymer> Examples of water-soluble polymers include cellulose derivatives (carboxymethylcellulose, methylcellulose, hydroxypropylcellulose, ethylcellulose), xanthan gum, xyloglucan, dextrin, dextran, carrageenan, locust bean gum, alginic acid, alginates, pullulan, starch, potato starch, kudzu starch, corn starch, gum arabic, locust bean gum, gellan gum, polydextrose, pectin, chitin, water-soluble chitin, chitosan, casein, albumin, soy protein lysate, peptone, tamarind gum, guar gum, etc. Among these, cellulose derivatives are preferred in terms of affinity with carboxymethylated cellulose nanofibers, and carboxymethylcellulose and its salts are particularly preferred. It is believed that water-soluble polymers such as carboxymethylcellulose and its salts penetrate between carboxymethylated cellulose nanofibers and increase the distance between the nanofibers, thereby improving redispersibility.
[0036] When carboxymethylcellulose or a salt thereof is used as the water-soluble polymer, it is preferable to use carboxymethylcellulose with a degree of carboxymethyl group substitution per anhydrous glucose unit of 0.55 to 1.6, more preferably 0.55 to 1.1, and even more preferably 0.65 to 1.1. In addition, a molecule with a long length (high viscosity) is preferable because it has a high effect of widening the distance between nanofibers. In addition, the B-type viscosity of a 1% by mass aqueous solution of carboxymethylcellulose at 25°C and 60 rpm is preferably 3 mPa·s to 14000 mPa·s, more preferably 7 mPa·s to 14000 mPa·s, and even more preferably 1000 mPa·s to 8000 mPa·s. Note that the "carboxymethylcellulose or a salt thereof" as the water-soluble polymer referred to here is completely dissolved in water, and is therefore distinguished from the carboxymethylated cellulose nanofibers whose fiber shape can be confirmed in water.
[0037] The blending amount of the water-soluble polymer is preferably 5% by mass to 300% by mass, more preferably 20% by mass to 300% by mass, even more preferably 25% by mass to 200% by mass, and even more preferably 25% by mass to 60% by mass, relative to the cellulose nanofiber (bone dry solid content). EXAMPLES
[0038] The present invention will be described in more detail below by way of examples, but the present invention is not limited to these.
[0039] (Method for measuring degree of carboxymethyl substitution) 1) Accurately weigh out approximately 2.0 g of carboxymethylated cellulose fiber (bone dry) and place it in a 300 mL Erlenmeyer flask with a stopper. 2) Add 100 mL of a solution of 100 mL of special-grade concentrated nitric acid to 1000 mL of nitric acid methanol, shake for 3 hours, and convert the carboxymethyl cellulose salt (carboxymethyl cellulose) into hydrogen-type carboxymethyl cellulose. 3) Accurately weigh out 1.5 to 2.0 g of hydrogenated carboxylated cellulose (bone dry) and place it in a 300 mL Erlenmeyer flask with a stopper. 4) Wet the hydrogenated carboxylated cellulose with 15 mL of 80% methanol, add 100 mL of 0.1 N NaOH, and shake at room temperature for 3 hours. 5) Back-titrate excess NaOH with 0.1N H2SO4 using phenolphthalein as an indicator. 6) The degree of carboxymethyl substitution (DS) is calculated by the following formula: A = [(100 × F'-(0.1N H2SO4) (mL) × F) × 0.1] / (bone-dry mass of hydrogenated carboxylated cellulose (g)) DS = 0.162 x A / (1-0.058 x A) A: The amount of 1N NaOH required to neutralize 1 g of hydrogenated carboxymethyl cellulose (mL) F': Factor of 0.1N H2SO4 F: Factor of 0.1N NaOH
[0040] (Method of measuring average fiber diameter and aspect ratio) The average fiber diameter and average fiber length of CNF were analyzed for 200 randomly selected fibers using an atomic force microscope (AFM). The aspect ratio was calculated using the following formula: Aspect ratio = average fiber length / average fiber diameter
[0041] [Example 1] (Preparation of carboxymethylated cellulose nanofibers) In a 5L twin-shaft kneader with the rotation speed adjusted to 100 rpm, 1089 parts of isopropanol (IPA) and 31 parts of sodium hydroxide dissolved in 121 parts of water were added, and 200 parts of hardwood pulp (LBKP, manufactured by Nippon Paper Industries Co., Ltd.) were added in terms of dry mass when dried at 100 ° C for 60 minutes. The mixture was stirred and mixed at 30 ° C for 60 minutes to prepare mercerized cellulose. 117 parts of sodium monochloroacetate were further added while stirring, and after stirring at 30 ° C for 30 minutes, the mixture was heated to 70 ° C over 30 minutes and carboxymethylation reaction was carried out at 70 ° C for 60 minutes. The proportion of water in the reaction medium during the mercerization reaction and the carboxymethylation reaction was 10 mass%. After the reaction was completed, the mixture was neutralized, washed with 65% water-containing methanol, deliquored, dried, and pulverized to obtain a sodium salt of carboxymethylated cellulose with a carboxymethyl substitution degree of 0.27 and a crystallinity of cellulose I type of 64%. The methods for measuring the degree of carboxymethyl substitution and the crystallinity of cellulose type I are as described above. The obtained sodium salt of carboxymethyl cellulose was dispersed in water to obtain a 1% (w / v) aqueous dispersion. This was treated three times with a high-pressure homogenizer at 150 MPa to obtain a dispersion of carboxymethyl cellulose nanofibers. The obtained carboxymethyl cellulose nanofibers had an average fiber diameter of 3.2 nm and an aspect ratio of 40. The obtained carboxymethylated cellulose nanofibers were dispersed in water to a solid content of 0.7% by mass, and carboxymethyl cellulose (manufactured by Nippon Paper Industries Co., Ltd., product name: F350HC-4, viscosity (1% by mass, 25°C, 60 rpm) approximately 3000 mPa·s, degree of carboxymethyl substitution approximately 0.90) was added at 40% by mass relative to the carboxymethyl cellulose nanofibers (i.e., so that the solid content of carboxymethyl cellulose was 40 parts by mass when the solid content of the carboxymethylated cellulose nanofibers was 100 parts by mass), and the mixture was stirred for 60 minutes with a TK homomixer (12,000 rpm). To this dispersion, 0.5% by mass of sodium hydroxide solution was added to adjust the pH to 9, and then the mixture was applied to the drum surface of a drum dryer D0405 (manufactured by Katsuragi Kogyo Co., Ltd.) and dried at 140°C for 1 minute. The resulting dried product was scraped off and then pulverized using an impact mill at a rate of 10 kg per hour to obtain a dried pulverized product with a moisture content of 5% by mass. The pulverized product was classified using a 30 mesh to obtain a powder containing carboxymethylated cellulose nanofibers and carboxymethyl cellulose (CNF powder).
[0042] (Production of Mizuyokan) 1g of the above CNF powder was added to the raw material for Mizuyokan, which was a mixture of 300g of commercially available red bean paste, 20g of sugar, 4g of agar, and 500g of water, and then the mixture was stirred at 5000 rpm using a TK homomixer, heated to dissolve the agar, and then poured into a mold and cooled in a refrigerator. When the completed Mizuyokan was observed, the red bean grains were uniformly dispersed and it looked excellent. This was tasted by 10 panelists, who rated the flavor on a scale of 1 to 10, scoring 8 to 10 for excellent flavor.
[0043] [Comparative Example 1] Mizu-yokan was produced in the same manner as in Example 1, except that no CNF powder was added. When the finished Mizu-yokan was observed, the red bean grains had settled to the bottom, and it looked poor. This was sampled by 10 panelists, who rated the flavor on a scale of 1 to 10, scoring 4 to 7 points.
Claims
[Claim 1] A yokan (jelly) containing carboxymethylated cellulose nanofiber and carboxymethyl cellulose or a salt thereof, The carboxymethylated cellulose nanofiber has a degree of carboxymethyl substitution in the range of 0.01 to 0.50; The carboxymethyl cellulose or a salt thereof has a degree of carboxymethyl substitution in the range of 0.55 to 1.6, and a Brookfield viscosity of a 1% by mass aqueous solution of the carboxymethyl cellulose at 25°C and 60 rpm in the range of 3 to 14,000 mPa s, The yokan contains the carboxymethyl cellulose or a salt thereof in an amount ranging from 25% by mass to 60% by mass relative to the carboxymethyl cellulose nanofiber (bone dry solid content).
Citation Information
Patent Citations
Soft adzuki-bean jelly-like filling
JP2007202520A
Food containing cellulose nanofiber, and method for producing the same
JP2013236585A
Emulsifier composition
JP2019156825A
Welan gum-containing composition
WO2017030206A1
Additive for food
WO2017199924A1